Comparative Analysis between Intravenous Ondansetron and Granisetron in Attenuation of Hypotension during Spinal Anaesthesia in Patients Undergoing Caesarean Section - B, Uma R. (Academia Anesthesiologica International, 2022)
Background: The aim was to evaluate the Ondansetron and Granisetron to avert hypotension and bradycardia induced by spinal anesthesia within subjects that required to undergo cesarean sections. Subjects and Methods: One Hundred and five patients were incorporated in the research. Subjects were separated into 3 groups group A (n=35) consist subjects that acknowledged intravenous 4 mg Ondansetron that was diluted in normal saline, Group B consist subjects that got intravenous 1 mg Granisetron that was diluted in normal saline and group C (n=35) got 10 ml intravenous normal saline 5 minutes earlier to subarachnoid Block. Results: All groups were statistically analogous to baseline systolic blood pressure (SBP). It was considerably fewer in Granisetron group as contrast to Ondansetron group 5 minutes. Diastolic blood pressure was statistically analogous amid all groups at baseline. The mean blood pressure was statistically similar amid the 3 groups at baseline. Conclusion: Intravenous Ondansetron 4 mg administrations earlier to spinal anaesthesia reduce the events of hypotension, bradycardia and vasopressor necessity in LSCS Subjects. Granisetron had no consequence on haemodynamic factors. There were considerably fewer occurrences of postoperative Nausea and Vomiting in Ondansatron and Granisetron group.